A Range Based Localization Error Minimization Technique for Wireless Sensor Network - Sudha H. Thimmaiah; Mahadevan G (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Wireless sensor network (WSN) is composed of low cost, tiny sensor that communicates with each other and transmit sensory data to its base station/sink. The sensor network has been adopted by various industries and organization for their ease of use and is considered to be the most sorted future paradigm. The sensor devices are remotely deployed and powered by batteries. Preserving the energy of sensor devices is most desired. To preserve the battery efficient routing technique is needed. Most routing technique required prior knowledge of sensor nodes location in order to provide energy efficiency. Many existing technique have been proposed in recent time to determine the position of sensor nodes. The existing technique proposed so for suffers in estimating the likelihood of localization error. Reducing the error in localization is most desired. This work present a (Time-of-Arrival) based localization technique and also present adaptive information estimation model to reduce/approximate the localization error in wireless sensor network. The author compares our proposed localization model with existing protocol and analyses its efficiency.